2019
DOI: 10.14569/ijacsa.2019.0100323
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Approach for Predicting Nicotine Dependence

Abstract: An examination of the ability of machine learning methodologies in classifying women Waterpipe (WP) smoker's level of nicotine dependence is proposed in this work. In this study, we developed a classifier that predicts the level of nicotine dependence for WP tobacco female smokers using a set of novel features relevant to smokers including age, residency, and educational level. The evaluation results show that our approach achieves a recall of 82% when applied on a dataset of female WP smokers in Jordan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Algorithms performance evaluation. In order to reduce outlier effects in the final decision of each algorithm, we calculated the mean values and standard-deviation (m±SD) of the following metrics: accuracy (ACCU), sensitivity (SENS), specificity (SPE), predictive positive value (PPV) and area under the receiver operating characteristic curve (AUC) [14,[39][40][41].…”
Section: Data Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Algorithms performance evaluation. In order to reduce outlier effects in the final decision of each algorithm, we calculated the mean values and standard-deviation (m±SD) of the following metrics: accuracy (ACCU), sensitivity (SENS), specificity (SPE), predictive positive value (PPV) and area under the receiver operating characteristic curve (AUC) [14,[39][40][41].…”
Section: Data Selectionmentioning
confidence: 99%
“…Previous studies show that for smokers, ML application showed good results in the empirical study of smoking cessation intervention in Korea (precision between 67.3% and 87.7%) [ 15 ], and nicotine dependence evaluation in Jordanian women (precision of 82.0%) [ 13 ]. However, in Brazilian healthcare services, the ML application for screening of patients is scarce and as far as we know it was used only in the cardiovascular risk evaluation [ 18 ], highlighting lack of screening of variables related to therapeutic intervention success (TIS) in Brazilian smokers using ML algorithms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection process is based on the predictor features that are known [4], [5]. Feature selection (FS), also known as attribute selection, is an essential phase of building any predictive model [6], [7]. This is essential since the number of features could be large and others less informative.…”
Section: Introductionmentioning
confidence: 99%
“…Explaining research chronological, including research design, research procedure (in the form of algorithms, Pseudocode or other), how to test and data acquisition [7]- [17]. The description of the course of research should be supported references, so the explanation can be accepted scientifically [2], [6]. Figures 1-2 and Table 1 are presented center, as shown below and cited in the manuscript [7], [20]- [30].…”
mentioning
confidence: 99%